2011
DOI: 10.3171/2011.7.spine11194
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of poly(N-isopropylacrylamide)-g-polyethylene glycol and poly(N-isopropylacrylamide)-g-methylcellulose branched copolymers as injectable scaffolds for local delivery of neurotrophins and cellular transplants into the injured spinal cord

Abstract: Object The authors investigated the feasibility of using injectable hydrogels, based on poly(N-isopropylacrylamide) (PNIPAAm), lightly cross-linked with polyethylene glycol (PEG) or methylcellulose (MC), to serve as injectable scaffolds for local delivery of neurotrophins and cellular transplants into the injured spinal cord. The primary aims of this work were to assess the biocompatibility of the scaffolds by evaluating graft cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 51 publications
(68 reference statements)
1
29
0
Order By: Relevance
“…299,[305][306][307][308][309][310] However, PNIPAM notably shows cytotoxity and is non-biodegradable, 311 which limits its applications in vivo, even though PNIPAM with finite molecular weight can be eliminated via glomerular filtration without in vivo long-term accumulation. To overcome these drawbacks, PNIPAM hydrogels have been established as cell sheets to construct organized hepatocyte or endothelial mono-or multi-layers.…”
Section: Peg and Poly(n-isopropylacrylamide)mentioning
confidence: 98%
See 1 more Smart Citation
“…299,[305][306][307][308][309][310] However, PNIPAM notably shows cytotoxity and is non-biodegradable, 311 which limits its applications in vivo, even though PNIPAM with finite molecular weight can be eliminated via glomerular filtration without in vivo long-term accumulation. To overcome these drawbacks, PNIPAM hydrogels have been established as cell sheets to construct organized hepatocyte or endothelial mono-or multi-layers.…”
Section: Peg and Poly(n-isopropylacrylamide)mentioning
confidence: 98%
“…Many researchers have prepared copolymers containing PEG and PNIPAM as forms including grafting, diblock, triblock, multiblock, and star. [299][300][301][302] Solutions of PEG-PNIPAM copolymers exhibit adequate injection viscosities, high hydrogel strengths, and rapid gelation kinetics. PEG-PNIPAM copolymers form liquid solutions at ambient temperature and become relatively strong elastic hydrogels at body temperature that display unique micelle aggregation behavior in aqueous solutions.…”
Section: Peg and Poly(n-isopropylacrylamide)mentioning
confidence: 98%
“…Alternatively, engineered cells producing specific regenerative factors can be delivered without the need for repeated administration, as would be required for the direct delivery of 'naked' protein [Conova et al, 2011;Bearat et al, 2012]. The same requirements that make hydrogels suitable for in situ gelation -compatibility with aqueous, noncytotoxic chemistries -enable the hydrogel-mediated delivery of live cells, where cells are embedded in the liquid hydrogel precursor prior to injection and in situ crosslinking [Lu et al, 2012;Liang et al, 2013;Mothe et al, 2013].…”
Section: Delivery Of Therapeutic Agentsmentioning
confidence: 99%
“…6 Our recent in vivo research using PNIPAAm- g -PEG showed that the hydrogel is biocompatible, can be successfully injected into an injury site and gelled in situ to fill and remain in a spinal cord lesion, without contributing to an injury-related inflammatory response. 7 The LCST of PNIPAAm- g -PEG of approximately 32°C allows it to be injected as a viscous liquid at room temperature and solidify in situ without the use of toxic monomers or cross-linkers. 38 …”
mentioning
confidence: 99%
“…Since our prior work indicated that PNIPAAm- g -PEG is permissive to axonal growth with the addition of BDNF, 7 we hypothesized that a BDNF-induced enhancement in the RST response would promote growth of RST axons into and beyond a hydrogel implant, aiding in accelerated functional recovery following a cervical lesion. To assess this, we combined an implant of PNIPAAm- g -PEG copolymer with codissolved BDNF to aid in the promotion of RST axon regeneration following a cervical dorsolateral funiculotomy.…”
mentioning
confidence: 99%